A type of A,B site doped perovskite Sr y Ca 1-y Ru x Ir 1-x O3, preparation methods and applications

CN116970978BActive Publication Date: 2026-10-16JILIN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310667532.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2026-10-16
Estimated Expiration
2043-06-07

AI Technical Summary

Technical Problem

然而,限制其广泛应用的主要因素是酸性条件下Ru基和Ir基催化剂的稀缺性和高成本

Benefits of technology

[0014] This invention has the following innovative features compared to existing technologies:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116970978B_ABST
    Figure CN116970978B_ABST
Patent Text Reader

Abstract

A, B site double-doped perovskite Sr y Ca 1‑y Ru x Ir 1‑ x O3 catalyst, preparation method and application thereof in electrocatalytic oxygen evolution reaction under acidic conditions, belong to the technical field of catalyst synthesis and electrocatalytic water splitting application technology.The perovskite oxide SrRuO3 is an anchoring matrix, citric acid, strontium acetate and calcium carbonate are dissolved in deionized water, and then a mixed solution of potassium hexachloroiridate, ruthenium trichloride hydrate and ethylene glycol is added, dried and calcined in stages at different temperatures, treated with hydrochloric acid to remove impurities, and the target catalyst is obtained.The catalyst can reach a current density of 10mA / cm 2 2 only needs 172mV in 0.5M H2SO4, and can reach a stability of more than 75h.The catalyst improves the problem that the catalyst is easily corroded under strong acid and strong oxidation conditions, and improves the energy conversion efficiency of electric energy into chemical energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of catalyst synthesis and electrocatalytic water splitting, specifically relating to an A,B site doped perovskite Sr y Ca 1-y Ru x Ir 1-x O3 catalyst, preparation method and its application in the electrocatalytic oxygen evolution reaction under acidic conditions. Background Technology

[0002] Hydrogen energy plays a crucial role in balancing economic development with massive energy consumption. Proton exchange membrane electrolyzers (PEMWE) and alkaline water electrolyzers (AWE) are two commonly used hydrogen production technologies. PEMWE addresses the problems of high energy consumption, relatively low hydrogen purity, and poor safety associated with alkaline water electrolyzers, offering advantages such as high overall efficiency and faster dynamic response. In particular, its ability to effectively inhibit electron transfer improves the electrolyzer's safety, allowing it to adapt to the volatility of renewable energy generation. Based on these characteristics, PEMWE is a more promising large-scale water splitting technology for industrial applications. Unfortunately, the slow kinetics and less-than-ideal stability of PEMWE's anode OER reaction limit its overall energy conversion efficiency. Therefore, finding a highly efficient and durable acidic OER catalyst is of great significance.

[0003] Currently known highly active transition metal oxides exhibit poor performance under acidic conditions. Compared to most catalysts, Ru and Ir-based catalysts demonstrate unparalleled catalytic activity in acidic electrolytes. However, the main factors limiting their widespread application are the scarcity and high cost of Ru-based and Ir-based catalysts under acidic conditions. Notably, Ir-based catalysts exhibit higher corrosion resistance under acidic conditions, but their global reserves are extremely low and their catalytic activity is generally limited; Ru-based catalysts possess extremely strong catalytic activity, but they are highly susceptible to dissolution during OER processes. To reduce the cost of PEM (proton exchange membrane) electrolyzers, improve catalyst utilization, and address the issue of poor catalyst corrosion resistance, the synthesis of polymetallic oxides for acidic OER is an urgent problem to be solved.

[0004] This invention proposes a dual-doped perovskite oxide Sr with different ions embedded at the A and B sites in the ABO3 perovskite lattice. y Ca 1-y Ru x Ir 1-xO3 exhibits excellent catalytic performance under acidic conditions, but we have not yet found any reports on the synthesis of this material or its application in the electrocatalytic oxidation of acidic water. This material demonstrates excellent oxygen production performance under 0.5 M H2SO4 conditions, achieving a current density of 10 mA cm⁻¹ at a voltage of 1.42 V. -2 Furthermore, this activity can be maintained for more than 75 hours, and its catalytic performance is superior to that of commercial RuO2 and IrO2. Summary of the Invention

[0005] This invention aims to improve energy conversion efficiency and promote the development of the hydrogen economy. It proposes a double-doped perovskite oxide, Sr, in which different ions are embedded at the A and B sites in the ABO3 perovskite lattice. y Ca 1-y Ru x Ir 1-x O3 catalyst, preparation method and its application in the electrocatalytic oxygen evolution reaction under acidic conditions.

[0006] The present invention describes a perovskite oxide Sr doped at both A and B sites. y Ca 1-y Ru x Ir 1-x The preparation method of O3 catalyst involves first dissolving citric acid, strontium acetate, and calcium carbonate in deionized water, then adding the solutions to a mixed solution of potassium hexachloroiridate, ruthenium trichloride hydrate, and ethylene glycol, and magnetically stirring to obtain a homogeneous solution. The resulting solution is then dried at 130–180°C for 10–20 h to obtain a brown solid precursor. This precursor is then calcined in air at 180–220°C for 5–8 h, 280–320°C for 5–8 h, 480–520°C for 2–5 h, and 680–720°C for 5–8 h, respectively. Finally, the obtained solid product is soaked in 1M hydrochloric acid for 5–8 h to remove impurities, thereby obtaining an A,B site doped perovskite oxide, Sr. y Ca 1-y Ru x Ir 1-x O3 catalyst.

[0007] In the above method, y is the molar mass of Sr and x is the molar mass of Ru.

[0008] In the above method, n 柠檬酸 :n 乙酸锶+碳酸钙 =1~2:1.

[0009] In the above method, n 乙酸锶+碳酸钙 :n 六氯乙酸钾+三氯化钌 =7~10:1.

[0010] In the above method, x = 0.2 to 0.8, y = 0.2 to 0.8; the heating rate during calcination is 2 to 4 °C / min.

[0011] In the above method, there are no requirements on the amount of deionized water and ethylene glycol used, as long as they are sufficient to dissolve the added solid substances.

[0012] The present invention describes a perovskite oxide Sr doped at both A and B sites. y Ca 1-y Ru 0.66 Ir 0.34 The O3 catalyst is prepared by the method described above.

[0013] The present invention describes a perovskite oxide Sr doped at both A and B sites. y Ca 1-y Ru 0.66 Ir 0.34 O3 catalysts can be used in the electrocatalytic oxygen evolution reaction under acidic conditions.

[0014] This invention has the following innovative features compared to existing technologies:

[0015] 1. Synthesis of high-performance, crystal-structure-stable, and relatively low-cost dual-doped perovskite-type multimetallic oxides Sr y Ca 1-y Ru x Ir 1-x O3, resulting in a double-doped perovskite-type metal oxide Sr y Ca 1-y Ru x Ir 1-x O3 nanocubes with slight defects.

[0016] 2. The obtained double-doped perovskite oxide Sr y Ca 1-y Ru x Ir 1-x O3 contains a certain amount of oxygen vacancies.

[0017] 3. The obtained double-doped perovskite oxide Sr y Ca 1-y Ru x Ir 1-x O3 material is a novel electrocatalytic water splitting catalyst that, while reducing the precious metal content in the catalyst, exhibits catalytic performance surpassing commercial IrO2 and RuO2 catalysts. In a 0.5 M H2SO4 solution, it achieves an oxygen production overpotential of 10 mA / cm² at 172 mV. 2 The current density is high, and the performance is stable for 75 hours (the smaller the overpotential, the better the oxygen evolution ability).

[0018] 4. The obtained double-doped perovskite oxide Sr y Ca 1-y Ru x Ir 1-x O3 catalysts improve the problem of catalysts being easily corroded under strong acid and strong oxidation conditions, while also improving the energy conversion efficiency of electrical energy to chemical energy, which plays a vital role in promoting the development of dual-carbon goals. Attached Figure Description

[0019] Figure 1 The A,B site co-doped perovskite Sr obtained in Example 1 0.66 Ca 0.34 Ru 0.66 Ir 0.34 XRD pattern of O3 catalyst material;

[0020] Figure 2 The A,B site double-doped perovskite Sr obtained in Example 1 0.66 Ca 0.34 Ru 0.66 Ir 0.34 SEM images of O3 catalyst materials;

[0021] Figure 3 The A,B site double-doped perovskite Sr obtained in Example 1 0.66 Ca 0.34 Ru 0.66 Ir 0.34 TEM image of O3 catalyst material;

[0022] Figure 4 The A,B site double-doped perovskite Sr obtained in Example 1 0.66 Ca 0.34 Ru 0.66 Ir 0.34 O1s XPS image of O3 catalyst material;

[0023] Figure 5 The A,B site double-doped perovskite Sr obtained in Example 1 0.66 Ca 0.34 Ru 0.66 Ir 0.34 Polarization curves of O3 catalyst material for oxygen production in 0.5M H2SO4;

[0024] Figure 6 The A,B site double-doped perovskite Sr obtained in Example 1 0.66 Ca 0.34 Ru 0.66 Ir 0.34 Catalytic stability curves of O3 catalyst materials. Detailed Implementation

[0025] The present invention will be further described below with reference to the accompanying drawings and embodiments, but the scope of protection of the present invention is not limited to the following embodiments.

[0026] Example 1

[0027] Solution 1 was prepared by mixing 39 mg (0.39 mmol) of calcium carbonate, 160.45 mg (0.78 mmol) of strontium acetate, and 280 mg (1.46 mmol) of citric acid with 5 mL of deionized water. Solution 2 was prepared by mixing 23 mg (0.11 mmol) of ruthenium trichloride hydrate, 26.7 mg (0.055 mmol) of potassium hexachloroiridate with 4 mL of ethylene glycol. Solution 2 was added dropwise to solution 1 and magnetically stirred for 3 hours to obtain a homogeneous mixed solution 3. Solution 3 was then transferred to an oven and dried at 150 °C for 12 h to obtain a brown solid precursor. The obtained brown solid precursor was placed in a quartz tube and placed in a tube furnace. It was then calcined in an atmosphere at a sequential gradient of 200 °C (6 h), 300 °C (6 h), 500 °C (3 h), and 700 °C (6 h) (heating rate of 3 °C / min). The calcined product was then subjected to 1 M... Immersion in HCl for 6 hours yields A,B site doped perovskite oxide Sr 0.66 Ca 0.34 Ru 0.66 Ir 0.34 O3 catalyst, product mass 15mg.

[0028] The materials prepared by the above method were subjected to some structural characterization. Figure 1 The XRD pattern of the obtained material is consistent with that of the simulated double perovskite. Figure 2 The image shows the SEM spectrum of the obtained material, which is a cube with slight etching. Figure 3 The TEM image of the obtained material shows that it has good crystallinity. Figure 4 The O1s XPS spectrum of the obtained material shows that the catalyst has a certain amount of oxygen vacancies.

[0029] The electrocatalytic oxygen production properties of the materials prepared by the above method were tested in a standard three-electrode electrolytic cell; the working electrode in the electrolytic cell was a perovskite oxide Sr doped at both A and B sites. 0.66 Ca 0.34 Ru 0.66 Ir 0.34 O3, the reference electrode is a saturated calomel electrode, and the counter electrode is a platinum wire.

[0030] Catalytic activity test: Figure 5The oxygen evolution polarization curve was measured under 0.5 M H₂SO₄ conditions. At an overpotential of 172 mV, the current density of this material reached 10 mA / cm². 2 .

[0031] Catalytic stability test: Figure 6 The stability curve was measured under 0.5M H2SO4 conditions. After 75 hours of operation, its catalytic performance showed almost no decline.

[0032] Example 2

[0033] Example 1 is basically the same, except that n needs to be noted. 柠檬酸 :n 乙酸锶+碳酸钙 =1:1 (At this point, citric acid is 225mg, ruthenium trichloride hydrate is 23mg, potassium hexachloroiridate is 26.7mg, calcium carbonate is 39mg, and strontium acetate is 160.45mg).

[0034] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 195 mV, the current density of this material reaches 10 mA / cm². 2 Moreover, after 70 hours of operation, its catalytic performance showed almost no decline.

[0035] Example 3

[0036] Example 1 is basically the same, except that n needs to be noted. 柠檬酸 :n 乙酸锶+碳酸钙 =2:1 (At this point, citric acid is 450mg, ruthenium trichloride hydrate is 23mg, potassium hexachloroiridate is 26.7mg, calcium carbonate is 39mg, and strontium acetate is 160.45mg).

[0037] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 197 mV, the current density of this material reaches 10 mA / cm². 2 Moreover, after 72 hours of operation, its catalytic performance showed almost no decline.

[0038] Example 4

[0039] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.2, y = 0.2, that is, Sr 0.2 Ca 0.8 Ru 0.2 Ir 0.8O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 6.88 mg, potassium hexachloroiridate is 64.15 mg, calcium carbonate is 132.9 mg, and strontium acetate is 49.02 mg).

[0040] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 205 mV, the current density of this material reaches 10 mA / cm². 2 Furthermore, after 45 hours of operation, its catalytic performance showed almost no degradation.

[0041] Example 5

[0042] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.2, y = 0.5, that is, Sr 0.5 Ca 0.5 Ru 0.2 Ir 0.8 O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 6.88 mg, potassium hexachloroiridate is 64.15 mg, calcium carbonate is 141 mg, and strontium acetate is 68.54 mg).

[0043] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 201 mV, the current density of this material reaches 10 mA / cm². 2 Moreover, after 40 hours of operation, its catalytic performance showed almost no decline.

[0044] Example 6

[0045] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.2 and y = 0.8, that is, Sr 0.8 Ca 0.2 Ru 0.2 Ir 0.8 O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 17.22 mg, potassium hexachloroiridate is 40.1 mg, calcium carbonate is 33.22 mg, and strontium acetate is 196.1 mg).

[0046] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 185 mV, the current density of this material reaches 10 mA / cm². 2 Moreover, after 40 hours of operation, its catalytic performance showed almost no decline.

[0047] Example 7

[0048] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.5 and y = 0.2, i.e., Sr 0.2 Ca 0.8 Ru 0.5 Ir 0.5 O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 17.22 mg, potassium hexachloroiridate is 40.1 mg, calcium carbonate is 132.9 mg, and strontium acetate is 49.02 mg).

[0049] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 190 mV, the current density of this material reaches 10 mA / cm². 2 Moreover, after 41 hours of operation, its catalytic performance showed almost no decline.

[0050] Example 8

[0051] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.5, y = 0.5, that is, Sr 0.5 Ca 0.5 Ru 0.5 Ir 0.5 O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 17.22 mg, potassium hexachloroiridate is 40.1 mg, calcium carbonate is 141 mg, and strontium acetate is 68.54 mg).

[0052] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 187 mV, the current density of this material reaches 10 mA / cm². 2 Furthermore, after 35 hours of operation, its catalytic performance showed almost no degradation.

[0053] Example 9

[0054] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.5 and y = 0.8, that is, Sr 0.8 Ca 0.2 Ru 0.5 Ir 0.5O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 17.22 mg, potassium hexachloroiridate is 40.1 mg, calcium carbonate is 33.22 mg, and strontium acetate is 196.1 mg).

[0055] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 185 mV, the current density of this material reaches 10 mA / cm². 2 Furthermore, after 55 hours of operation, its catalytic performance showed almost no degradation.

[0056] Example 10

[0057] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.66 and y = 0.2, that is, Sr 0.2 Ca 0.8 Ru 0.66 Ir 0.34 O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 23 mg, potassium hexachloroiridate is 26.7 mg, calcium carbonate is 132.9 mg, and strontium acetate is 49.02 mg).

[0058] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 183 mV, the current density of this material reaches 10 mA / cm². 2 Moreover, after 51 hours of operation, its catalytic performance showed almost no decline.

[0059] Example 11

[0060] Basically the same as Example 1, except that attention should be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.66 and y = 0.5, that is, Sr 0.5 Ca 0.5 Ru 0.66 Ir 0.34 O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 23 mg, potassium hexachloroiridate is 26.7 mg, calcium carbonate is 141 mg, and strontium acetate is 68.54 mg).

[0061] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 189 mV, the current density of this material reaches 10 mA / cm². 2 Moreover, after 20 hours of operation, its catalytic performance showed almost no decline.

[0062] Example 12

[0063] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.66 and y = 0.8, that is, Sr 0.8 Ca 0.2 Ru 0.66 Ir 0.34 O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 23 mg, potassium hexachloroiridate is 26.7 mg, calcium carbonate is 33.22 mg, and strontium acetate is 196.1 mg).

[0064] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 200 mV, the current density of this material reaches 10 mA / cm². 2 Furthermore, after 37 hours of operation, its catalytic performance showed almost no degradation.

[0065] Example 13

[0066] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.8 and y = 0.2, i.e., Sr 0.2 Ca 0.8 Ru 0.8 Ir 0.2 O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 27.55 mg, potassium hexachloroiridate is 16.04 mg, calcium carbonate is 132.9 mg, and strontium acetate is 49.02 mg).

[0067] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 188 mV, the current density of this material reaches 10 mA / cm². 2 Furthermore, after 44 hours of operation, its catalytic performance showed almost no degradation.

[0068] Example 14

[0069] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.8 and y = 0.5, that is, Sr 0.5 Ca 0.5 Ru 0.8 Ir 0.2O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 27.55 mg, potassium hexachloroiridate is 16.04 mg, calcium carbonate is 141 mg, and strontium acetate is 68.54 mg).

[0070] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 191 mV, the current density of this material reaches 10 mA / cm². 2 Moreover, after 56 hours of operation, its catalytic performance showed almost no decline.

[0071] Example 15

[0072] Example 1 is basically the same, except that attention needs to be paid to Sr y Ca 1-y Ru x Ir 1-x In O3, x = 0.8, y = 0.8, that is, Sr 0.8 Ca 0.2 Ru 0.8 Ir 0.2 O3 (at this point, citric acid is 280 mg, ruthenium trichloride hydrate is 27.55 mg, potassium hexachloroiridate is 16.04 mg, calcium carbonate is 33.22 mg, and strontium acetate is 196.1 mg).

[0073] Electrocatalytic performance of the obtained sample: Under 0.5 M H2SO4 conditions, at an overpotential of 201 mV, the current density of this material reaches 10 mA / cm². 2 Moreover, after 61 hours of operation, its catalytic performance showed almost no decline.

[0074] The above embodiments are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes, substitutions and improvements that can be easily conceived by those skilled in the art within the spirit and principles of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A type of A,B site dual-doped perovskite Sr y Ca 1-y Ru x Ir 1-x The method for preparing O3 catalyst is characterized by: First, citric acid, strontium acetate, and calcium carbonate were dissolved in deionized water, and then added to a mixed solution of potassium hexachloroiridate, ruthenium trichloride hydrate, and ethylene glycol. The mixture was magnetically stirred to obtain a homogeneous solution. The resulting solution was dried at 130–180°C for 10–20 h to obtain a brown solid precursor. This precursor was then calcined in air at 180–220°C for 5–8 h, 280–320°C for 5–8 h, 480–520°C for 2–5 h, and 680–720°C for 5–8 h, respectively. Finally, the obtained solid product was soaked in 1M HCl for 5–8 h to remove impurities, thus obtaining the aforementioned A,B site-double-doped perovskite oxide Sr. y Ca 1-y Ru x Ir 1-x O3 catalyst, x = 0.2–0.8, y = 0.2–0.

8.

2. The A,B site dual-doped perovskite Sr as described in claim 1 y Ca 1-y Ru x Ir 1-x The method for preparing O3 catalyst is characterized by: n 柠檬酸 :n 乙酸锶+碳酸钙 = 1 to 2:1, where n represents the molar quantity.

3. The A,B site dual-doped perovskite Sr as described in claim 1 y Ca 1-y Ru x Ir 1-x The method for preparing O3 catalyst is characterized by: n 乙酸锶+碳酸钙 :n 六氯铱酸钾+三氯化钌 =7~10:1, where n represents the molar quantity.

4. The A,B site dual-doped perovskite Sr as described in claim 1 y Ca 1-y Ru x Ir 1-x The method for preparing O3 catalyst is characterized by: The heating rate during calcination is 2–4 °C / min.

5. A perovskite Sr doped at both A and B sites y Ca 1-y Ru x Ir 1-x O3 catalyst, characterized in that: It is prepared by the method described in any one of claims 1 to 4.

6. The A,B site dual-doped perovskite oxide Sr as described in claim 5 y Ca 1-y Ru 0.66 Ir 0.34 Application of O3 catalyst in electrocatalytic oxygen evolution reaction under acidic conditions.

Citation Information

Patent Citations

  • Iridium-based solid solution perovskite catalyst SrTi(Ir)O3 and application thereof in electrocatalytic water splitting for oxygen production

    CN109161926A

  • Network doped perovskite catalyst and preparation method and application thereof

    CN109967068A